Terminal sliding mode attitude-position quaternion based control of quadrotor unmanned aerial vehicle. Issue 9 (1st May 2023) - Serrano, Fernando; Castillo, Oscar; Alassafi, Madini; Alsaadi, Fawaz; Ahmad, Adil
Abstract: In this paper is presented the development of a terminal sliding mode attitude-position quaternion based control of a quadrotor unmanned aerial vehicle UAV. First, the dynamics of this UAV is divided into an attitude and position loop in order to design suitable independent control laws. The type of control law implemented for each loop is of the kind of hybrid terminal sliding mode and quaternion controller. The advantages of these control strategies over other techniques found in the literature are that the implementation of a quaternion based control strategy provides a relatively simple approach considering that the dynamics for the attitude and position loops can be described in this way. The quaternion based control strategy is suitable considering the kinematic and dynamic model of a quadrotor UAV, meanwhile the sliding mode controller part provides a relativelly simple control strategy taking into consideration that is reliable against uncertainties and provide a fast and accurate attitude-position tracking considering a reference to be followed by each loop. It is important to take into consideration that when an attitude command is given, the closed loop dynamics of the attitude block is stabilized generating at the same time the reference for the position loop. The terminal sliding mode controller part is obtained by selecting an appropriate sliding surface in order that the control law for each loop would be drove to the reaching phase faster and accurately. It is worthy to mention that both control loops posses feedforward neural networks as compensators in order that the tracking error will be reduced by both control strategies. Finally, a numerical experiment is conducted in order that the theoretical results are validated offering the appropriate discussion and conclusions about this research study.